2022
DOI: 10.3138/jmvfh-2021-0089
|View full text |Cite
|
Sign up to set email alerts
|

Desire to serve: Insights from Canadian defence studies on the factors that influence women to pursue a military career

Abstract: LAY SUMMARY The Canadian Armed Forces (CAF) continue to highlight the need to promote greater diversity and inclusion in its ranks. An increased representation of women in the Canadian military would enable greater capacity and capabilities to serve people, both domestically and abroad, and would contribute to a more diverse and inclusive military. To better understand how the CAF could increase the representation of women in the Canadian military, this article provides the key findings of three internal rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…Previous research has demonstrated that efforts to establish organizational responsibility for improving diversity were more effective at increasing managerial diversity than individual efforts such as mentoring and networking (Kalev et al, 2006). Our research provides further evidence that empowerment messaging increases the attributions of women’s burden to solve gender inequality in the workplace and its use should be reconsidered in the cultural discourse around workplace gender inequality, especially when known structural barriers are preventing the full participation of women (Schmidt & Cacace, 2019; Waruszynski et al, 2019), as they do in the CAF.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous research has demonstrated that efforts to establish organizational responsibility for improving diversity were more effective at increasing managerial diversity than individual efforts such as mentoring and networking (Kalev et al, 2006). Our research provides further evidence that empowerment messaging increases the attributions of women’s burden to solve gender inequality in the workplace and its use should be reconsidered in the cultural discourse around workplace gender inequality, especially when known structural barriers are preventing the full participation of women (Schmidt & Cacace, 2019; Waruszynski et al, 2019), as they do in the CAF.…”
Section: Discussionmentioning
confidence: 69%
“…One traditionally male-dominated institution that has been working to address gender inequality is the Canadian Armed Forces (CAF). Although the CAF has lifted the formal restrictions that previously limited women’s full participation (Davis, 2004), women still face barriers to equality, including a hostile, sexualized culture, lack of support for members who are parents, and stunted career progressions (Deschamps, 2015; Waruszynski et al, 2019). Acknowledging these barriers and the undesirable underrepresentation of women that they cause, in 2016, the CAF set a goal of increasing its complement of women from 15% to 25% by the year 2026 (Department of National Defence, 2017).…”
Section: Empowerment Messagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, gender stereotypes have touted military service as being almost synonymous with masculinity and maleness ( Goldstein, 2018 ; Deng et al, 2023 ). A masculinized culture can be perceived as an environment that perpetuates male ideologies, and social and cultural norms in a work environment, sometimes to the exclusion of women and other groups and communities (see Waruszynski et al, 2022 ). Combat roles are some of the most prestigious and exclusive occupations in any military organization, as they can be depicted as demonstrations of having ‘masculinized’ power over others ( Goldstein, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contending with the culture that has been created and maintained by the historically masculinized dominant group can be very challenging and can further generate multiple barriers for women wanting to succeed in military positions. Research has highlighted how servicewomen have had to portray themselves as “one of the boys” to fit in; reject notions of their femininity; work harder to prove themselves capable of doing the job; endure the negative perceptions of pregnancy and family responsibilities versus their capabilities and commitment to the armed forces; and challenge perceptions which attribute their success to their gender and not to their abilities (i.e., tokenism; Petite, 2008 ; King, 2016 ; Crowley and Sandhoff, 2017 ; Waruszynski et al, 2018 , 2022 ; Davis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%